Design of Floating Tourism Boat Using Barge Hull as Tourism Support in Ngipik Lake Gresik - Rusdiansyah, Firman (Universitas Muhammadiyah Gresik, 2025)
Gresik Regency is one of the Indonesian regions in East Java that has potential in the field of tourism that can be developed. Ngipik Lake is one of the attractions located in the center of Gresik. This final project intends to design a barge as a floating tourism so that later it can be a reference for ship owners regarding the conversion of barge functions and function as a reference for the development of Lake Ngipik tourism as an alternative tourist destination. The design process in question includes determining the main size of the ship which is adjusted to the rides and facilities in this floating tour, as well as determining the electricity needs as well as LWT and DWT components. From the technical analysis process, it was found that the appropriate size for floating tourism is L= 28.7 m, B= 16.4 m, H= 3.12 m, T= 2.12 m with a capacity of 250 people. Safety plan design with the addition of 255 lifejackets and 12 lifebouy.